Investigation of mixing effects of silicon isotopes under shave‐off condition using atom probe tomography. (28th July 2014) - Karasawa, Masanobu; Fujii, Makiko; Morita, Masato; Ishimura, Satoshi; Mayama, Norihito; Uchida, Hiroshi; Kawamura, Yoko; Itoh, Kohei M.; Owari, Masanori; Yurimoto, Hisayoshi
<x xml:space="preserve">Abstract</x> Shave‐off depth profiling uses a Ga focused ion beam micro‐machining process to provide highly precise depth profiles with nanometer‐scale resolution. This method is a very unique process for acquiring a depth profile using the shave‐off scan mode, in which the primary ion beam perpendicular to the direction of depth irradiates the sample. In our previous study, we confirmed by molecular dynamics simulation that the shave‐off scan mode has a low mixing effect compared with the conventional scan mode, which uses the normal incident angle. However, the current understanding of measurement using the shave‐off scan mode is insufficient. In this study, in order to estimate the sample damage in the shave‐off scan mode, we investigated the degree of mixing effects after the primary ion bombardment under shave‐off conditions using atom probe tomography. To evaluate the mixing effects, the intermixing of silicon isotope multilayers induced by ion beam irradiation was investigated. The depth of the damage from the sample surface caused by Ga focused ion beams was analyzed for both the shave‐off scan mode and the conventional scan mode using the normal incident angle. Results showed that the shave‐off scan mode has a significantly smaller mixing effect than the conventional scan mode. In addition, results showed that the attenuations of the damage and the Ga concentration exhibited almost the same tendency. Copyright © 2014 John Wiley & Sons, Ltd.